Antibacterial Activity of Pistacia vera L. Nuts and Extracted Lipophylic - Firas Al-Bayati; Hassan Faesal Al-Mola (College of Education for Pure Sciences, 2007)
Abstract The present study investigated antibacterial activities of different extracts from Pistacia vera nuts against Gram positive and negative bacteria using disc diffusion method, The Aqueous extract showed moderate effects against test bacteria specially on Bacillus cereus. Ethanol extract showed significant inhibitory effects against most bacteria compared with the standard antibiotics except Serratia marcescens and Salmonella typhimurium which resisted all concentrations of aqueous and ethanol extracts. Acetone extract showed less activity against test bacteria compared with ethanol extract, and the optimal concentration was 12.5mg/cm3 against Pseudomonas aeruginosa, The lipophylic extract was active against Staphylococcus aureus and Ps. aeruginosa and also the optimal concentration was 12.5mg/cm3 against Ps. aeruginosa, meanwhile no inhibitory effect was seen using lipophylic extract against Klebsiella pneumoniae, Salmonella typhimurium and Serr. marcescens.